ENHANCING EFL LEARNERS’ SPEAKING SKILLS THROUGH THE AUDIO-LINGUAL METHOD - Muhammad Ashari Putra; Didha Fridayanto; Bayu Prasetyo Aji; Sayit Abdul Karim; Suryo Sudiro (Journey: Journal of English Language and Pedagogy, 2022)
The teaching method is one of the contributing factors to successful English language learning. The appropriate use of a teaching method is one of the ways to enhance learners’ speaking skills. The present study aims at reviewing the use of the Audio-Lingual Method (ALM), one of the teaching methods to enhance EFL learners’ speaking skills. The present study employs library research to delineate the use of ALM to enhance learners' mastery of speaking skills. The data were obtained from documentation study and previous research findings and further analyzed qualitatively. Therefore, it reviews the brief of ALM, the purposes of ALM. Moreover, it scrutinizes the strategies used in ALM, the benefits of using and the implication of using ALM in classroom teaching. Finally, some important points on the use of ALM are highlighted in the conclusion part.